INFORMED CONSENT AS LEGAL LIABILITY MAFIA HEALTH MALPRACTICE - Suryono, Arief; Tsary, Syifa Rana (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to examine the conduct of doctors or medical personnel who commit mistakes or omissions in malpractice and harm the patient, as well as the form of justice stipulated by the law to the patient malpractice victims if informed consent has been agreed upon in advance. This research uses normative methods by examining library material or secondary data. The formulation of the problem that is examined is the reason why informed consent can be made a protector for doctors who do malpractice, and the principle of justice in informed consent for malpractice patients. The results of this research are doctors or medical personnel considered malpractice when conducting medical actions that violate standard service and operational standards of the procedure. However, it is difficult to prove the doctor’s fault and negligence, the patient or the patient’s family has consented to informed consent with any consequences that will occur. Informed consent has not yet upheld the principle of justice for malpractice patients because the patient’s legal efforts to protect its rights are not easy to do and Informed consent instead of providing legal immunity to doctors or medical personnel.